Odpowiedzi

2010-03-13T09:56:32+01:00
2x + 3 = 5(x-3)
2x+3 = 5x-15
2x-5x=15-3
-3x=-18 /: (-3)
x= 6


proszę bardzo, a to drugie nie ma sensu!
3 1 3
  • Użytkownik Zadane
2010-03-13T09:58:46+01:00
2x + 3y = 5(x-3)
4(x+5) -2 (y-3) = 34

2x+3y=5x-15
4x+20-2y+=34

-3x+3y=15
4x-2y=14

-x+y=5
2x-y=7
_______
x=13

-13+y=5
y=18

x=13
y=18
1 1 1
Najlepsza Odpowiedź!
2010-03-13T10:11:28+01:00
2x + 3y = 5(x-3)
4(x+5) -2 (y-3) = 34
2x+3y=5x-15
4x+20-2y+6=34
-3x+3y=-15 /*2
4x-2y=8 /*3
-6x+6y=-30
12x-6y=24
6x=-6
x=-1
2*(-1)+3y=-5-15
-2+3y=-20
3y=-18
y=-6
x=-1
2 5 2